BARROQUEIRO, Deana (2021), História dos Paladares, Lisboa, Prime Books. ISBN: 978-989-655-4293, 396 pp. - Sánchez Sánchez, Rosa Maria (História: revista da Faculdade de Letras da Universidade do Porto, 2022)
BARROQUEIRO, Deana (2021), História dos Paladares, Lisboa, Prime Books. ISBN: 978-989-655-4293, 396 pp.